Biomaterials recycling: a promising pathway to sustainability - Wiśniewska, Paulina; Saeb, Mohammad Reza; Bencherif, Sidi A. (Frontiers in Biomaterials Science, 2023)
Biomaterials undergo a transformative journey, from their origin as renewable resources to the manufacturing plants where they are processed and stored, until they fulfill their intended therapeutic or diagnostic purposes and become medical waste. However, during this life cycle, biomaterials can be susceptible to contamination and subsequent degradation through various mechanisms such as hydro-mechanical, thermal, or biochemical processes in water, soil, or air. These factors raise significant concerns regarding biological safety. Additional complexities arise from the potential amalgamation of biomaterials with other materials, either of the same kind or different types. Use of biomaterials influences their porosity, surface chemistry, and structural strength, and these factors affect biomaterials’ reusability. Given the multitude of materials, processing parameters, sustainability requirements, and the limitation of natural resources, the recycling of biomaterials becomes necessary. Unfortunately, this topic has received limited attention thus far. In this context, this perspective provides a brief overview, analysis, and classification of reports on biomaterials recycling, aiming to initiate a discussion on this frequently overlooked subject. We highlight the challenges related to energy consumption and environmental pollution. However, the lack of established protocols and reporting on biomaterials recycling prevents a comprehensive understanding of these challenges and potential solutions. Nevertheless, addressing these issues can lead to more efficient resource use and reduced environmental impact in the field of biomaterials.